Phosphate complexes of calix[4]pyrroles - Naulapää, Julia (2020)
This bachelor’s thesis is about the structure and the properties of different calix[4]pyrroles. Specifically, the binding of calix[4]pyrroles with different phosphate-containing molecules is assessed. These phosphate-binding properties are compared across different substituent-containing calix[4]pyrroles, using for example association constants. Some applications for the use of the complexes are also discussed